Analysis of Performance of Venture Capital Funds in Transition Countries: An Empirical Study in Bosnia and Herzegovina - Irena alić; Svetlana Terzić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
Many transition post-socialist countries still face the burden of the centrally planned economies. The new entrepreneurial society that is yet to be developed in these countries should be an association of people with pronounced individuality and different needs, with different rights and obligations. Capital markets in Southeast Europe, in recent years, become increasingly important as a leverage of the development of entrepreneurial societies. One of the most important new forms of financing is venture capital funds. These funds are especially important for the financing of start-up enterprises, which are trying to succeed utilizing modern high technologies. Since the newly formed enterprises have difficulties in getting favorable sources of financing, venture capital funds can have an important role in developing economies. In our study we focus on the current state of venture capital funds in Bosnia and Herzegovina as the representative of post-socialist transition countries. The main goal of this paper is to demonstrate the importance of venture capital for growth and development of small and medium-sized enterprises.
Keywords: G24; 330; transition; development; financing; venture capital funds; start-up; enterprise; management